Cross-Talk Between Antigen Presenting Cells and T Cells Impacts Intestinal Homeostasis, Bacterial Infections, and Tumorigenesis - Gaudino, Stephen J.; Kumar, Pawan (Frontiers in Immunology, 2019)
Innate immunity is maintained in part by antigen presenting cells (APCs) including dendritic cells, macrophages, and B cells. APCs interact with T cells to link innate and adaptive immune responses. By displaying bacterial and tumorigenic antigens on their surface via major histocompatibility complexes, APCs can directly influence the differentiation of T cells. Likewise, T cell activation, differentiation, and effector functions are modulated by APCs utilizing multiple mechanisms. The objective of this review is to describe how APCs interact with and influence the activation of T cells to maintain innate immunity during exposure to microbial infection and malignant cells. How bacteria and cancer cells take advantage of some of these interactions for their own benefit will also be discussed. While this review will cover a broad range of topics, a general focus will be held around pathogens, cancers, and interactions that typically occur within the gastrointestinal tract.